Nature and Management of Penetrating Spinal Cord Missile Injuries at Shree Birendra Hospital, Chhauni from November 2001 to November 2004 - Sharma, A P (Medical Journal of Shree Birendra Hospital, 2005)
Nature and Management of Penetrating Spinal Cord Missile Injuries at Shree Birendra Hospital, Chhauni from November 2001 to November 2004